1991
DOI: 10.1159/000288414
|View full text |Cite
|
Sign up to set email alerts
|

Job Stressors and Coping in Health Professions

Abstract: In spite of their knowledge about stressors, health hazards and coping, health professionals are in general not aware of their own health risks. In an attempt to clarify the issue results of our own studies are compared to the relevant literature. A survey on 1,248 Swiss nurses confirmed the major stressors known: ethical conflicts about appropriate patient care, team conflicts, role ambiguity, workload and organizational deficits. In doctors workload and shortage of time, combined with specific responsibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 17 publications
3
36
0
7
Order By: Relevance
“…The most common form of aggressive behaviors is psychological violence -mobbing, sexual harassment, intimidation. It takes place as long as people are forced to spend time together for a particular period of time, for example in the workplace, or school setting [2,[6][7][8]. Violence in the workplace does not only concern the involved individuals who experience physical injuries and long-lasting stress.…”
Section: Resultsmentioning
confidence: 99%
“…The most common form of aggressive behaviors is psychological violence -mobbing, sexual harassment, intimidation. It takes place as long as people are forced to spend time together for a particular period of time, for example in the workplace, or school setting [2,[6][7][8]. Violence in the workplace does not only concern the involved individuals who experience physical injuries and long-lasting stress.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a study in Iceland found nurses satisfied with their jobs and their assignment to shift work did not seem to disrupt their circadian cycle or induce any differences in their experience of illness [9]. The National Institute for Occupational Safety and Health in the United States nonetheless ranked nursing among the top 40 occupations with the highest prevalence of stress-related disorders [10]. Work-related stress can be defined as a pattern of emotional, cognitive, behavioral and physiological reactions to adverse and noxious aspects of work content, work organization and work environment [11].…”
Section: Instrumentmentioning
confidence: 99%
“…Finally, another area of concern with regards to the nursing profession is the well-documented adverse mental health problems associated with nursing. Rates of depression, anxiety, somatization, and burnout reported by nurses are among the highest of all the care-giving professions [15][16][17] . Burnout, in particular, has been associated with high rates of nurse dissatisfaction and turnover 18) .…”
Section: Introductionmentioning
confidence: 99%